Endangered species Crambe steveniana in vitro plant culture obtaining and the study of aseptic cultivation influence on its biochemistry - Пушкарьова, Н. О.; Каліста, М. С.; Белокурова, В. Б.; Кучук, М. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The study of endangered species Crambe steveniana aseptic in vitro culture establishing and definition of its fast microclonal propagation terms have been conducted. Fatty acid composition of vegetative parts of plants that were cultivated in vitro and in vivo along with their seeds was determined and compared. Seed surface sterilization was performed by the authors method with further morphogenic reaction of explants (lateral bud) on the presence in the medium of 6-benzylaminopurine (0,5–2 mg/L) study. Fatty acids content was determined using gas chromatography/mass spectrophotometry of fatty acid ethers obtained from seeds and green mass of plants that were cultivated in vitro and in vivo. Aseptic spouts culture of the studied species was established and optimal BA concentration (0,6 mg/L) in the medium was defined for fast multiplication of aseptic spouts. Fatty acid content increase was detected in the samples from aseptic plants compared with not aseptic ones. Also, high α-linolenic acid amount in the samples from both in vitro and in vivo grown plants was established. Significantly high erucic acid content was shown for seed samples.